Mathematical modelling of cemented tailings backfill: a review. Issue 6 (18th August 2019) - Cui, Liang; Fall, Mamadou
Abstract: This paper provides a comprehensive understanding and unique aspects of modelling cemented paste backfill (CPB) behaviour and performance under complex multiphysics conditions. Such modelling is essential for the reliable and cost-effective design of CPB structures. In this review paper, the existing mathematical models are classified into three categories, which are analytical, mechanical constitutive and coupled multiphysics models. For each category, a critical discussion of each model is carried out to identify its applicability and potential further developments with a comparison of the corresponding controlling mechanism. Then, a comparison of the existing models is provided for each category of mathematical models.